187k views
5 votes
T squared plus 5.4t plus 3.6 equals 0

User Gbero
by
4.6k points

1 Answer

1 vote

Answer:

The roots of the quadratic equation are.

t = -0.78

t = -4.62

Explanation:

Assume: we find the roots of the given quadratic equation.

Given:

the given expression is.

T squared plus 5.4t plus 3.6 equals 0

Rewrite the equation as.


t^(2)+5.4t+3.6=0

Now, we first find the root of the above equation.

Use quadratic formula with
a=1, b=5.4, c=3.6.


t=\frac{-b\pm \sqrt{(b)^(2)-4ac}}{2a}

Put a, b and c value in above equation.


t=\frac{-5.4\pm \sqrt{(5.4)^(2)-4(1)(3.6)}}{2(1)}


t=(-5.4\pm √(29.16-4* 3.6))/(2)


t=(-5.4\pm √(29.16-14.4))/(2)


t=(-5.4\pm √(14.76))/(2)


t=(-5.4\pm 3.84)/(2)

For positive sign


t=(-5.4 + 3.84)/(2)


t=(-1.56)/(2)

t = -0.78

For negative sign


t=(-5.4 - 3.84)/(2)


t=(-9.24)/(2)

t = -4.62

Therefore the roots of the quadratic equation t = -0.78 or t = -4.62

.

User Hgiasac
by
4.5k points